ANALYSIS OF REPRESENTATION OF CHARACTER EDUCATION VALUES IN CHILDREN'S SHORT STORIES BY CONTEMPORARY INDONESIAN AUTHORS - Dewi Anggraini; Hasbullah Ridwan (As-Sulthan Journal of Education, 2025)
This study aims to analyze the representation of character education values in children's short stories by contemporary Indonesian authors. This study is motivated by the importance of instilling character in children from an early age through media that is close to their world, one of which is through children's literature. The purpose of this study is to reveal how character values such as responsibility, honesty, empathy, and independence are represented contextually, especially through characters, conflicts, and story resolutions in contemporary children's short stories. This study uses a descriptive qualitative approach with a content analysis method. Data collection techniques are carried out through documentation of children's short stories published in the period 2015–2024 and interviews with elementary and junior high school teachers in Banyuwangi. The data analysis technique uses the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The results of the study show that character values in contemporary children's short stories are represented contextually and close to the world of children, appear strongly in the structure of conflict and story resolution, and feature independent and empowered child characters. These short stories are an effective medium in character education because they are able to build emotional involvement and moral reflection in child readers in a natural and enjoyable way.